Information Technology Utilization in the Practice of Shamanism during Covid-19" - Daulay, Pardamean Dame; Hunowui, Momy A. (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
The Practice of Shamanism Continues into Modern Society. To survive and grow, shamans follow the development of the times and continuously adapt to technological advancements. This research aims to explore the utilization of information technology in shamanic practices during the Covid-19 pandemic. The research method used is qualitative, using modernization theory. The results show the existence of shamanic practices utilizing information technology during the Covid-19 pandemic. The research subjects use features of information technology such as phone calls, video calls, and WhatsApp to provide services to their patients. Information technology is also used for promoting their services; they use Facebook and Instagram for this purpose. The utilization of information technology is done to increase the number of patients and to heal both mild and severe illnesses, including curing Covid-19 patients. Their patients feel comfortable because they do not have to travel far to meet with the shaman. This research concludes that the utilization of information technology has expanded into shamanic practices since the Covid-19 pandemic hit the world.